Arbuscular Mycorrhizal Fungi Increase Blast Resistance and Grain Yield in Japonica Rice Cultivars in Flooded Fields - Héctor Martín-Cardoso; Laia Castillo; Iratxe Busturia; Gerrit Bücker; Luís Marqués; Eva Pla; Mar Català-Forner; Concha Domingo; Blanca San Segundo (Rice)
Abstract Arbuscular mycorrhizal (AM) fungi establish symbiotic associations with a wide range of plant species. Root colonization by AM fungi improves the uptake of mineral nutrients in the host plant, mainly phosphorus, in exchange for photosynthetically fixed carbon. Rice is one of the most important cereal crops in the world that is cultivated in diverse ecosystems, mainly in flooded fields. Although rice is a host for AM fungi, flooding depresses colonization of rice roots by AM fungi. However, once fungal penetration into the rice root has occurred, the functional capacities of the AM fungus are not affected by flooding. In this study, we investigated mycorrhizal responsiveness in a panel of temperate japonica rice varieties in low fertility soil collected from rice fields. We show that inoculation with an AM fungus, either Rhizophagus irregularis or Funneliformis mosseae, stimulates seedling growth, improves Pi nutrition and enhances resistance to infection by the fungus Magnaporthe oryzae in aerobically grown rice plants in low fertility soil. The fungus M. oryzae is the causal agent of the rice blast disease, one of the most devastating diseases in cultivated rice worldwide. Field trials were conducted in flooded paddy fields of eastern Spain (mediterranean region) in 2023 and 2024. Three elite rice varieties were inoculated with R. irregularis and grown in nurseries under aerobic conditions during early vegetative stage. The AM-inoculated seedlings were then transplanted to flooded fields. We show that inoculation with R. irregularis increases grain yield and blast resistance, namely leaf blast, neck blast, node blast and panicle blast, in flooded field conditions. Although all the japonica rice varieties here examined benefited from the AM symbiosis, its effects varied depending on the rice variety and the geographical location. These findings demonstrated that the application of AM fungi in nurseries may be integrated with conventional rice cultivation systems in paddy fields for the development of sustainable rice production systems less dependent on chemical fertilizers and pesticides.